CRYPTOCURRENCY MINING EFFECTS ANALYSIS ON SEMICONDUCTOR SHORTAGE ON PC OWNER COMMUNITY - Hendra Wijaya Lim; Tony Wibowo (Universitas Internasional Batam, 2022)
Cryptocurrency is a revolutionary peer to peer transaction method which utilize Block chain technology to enable frictionless transaction across the globe with relatively low fees. As Block chain technology goes mainstream, several problems had emerged, one of these problems are semiconductor shortage caused by booming popularity of such Cryptocurrency mining. Which cause widespread problems in the whole world, crippling not only technology industries and spilling to other industries such as car industries and electronic industries. In this study, we delved into what causes these problems and how and what will help solve these problems that are occurring in the market, in this research used Case study model for this phenomenon and came into conclusion that cryptocurrency mining will not last long and shortages maybe easing.